The effect of nurse-led interventions in self-efficacy and psychosocial adjustment of individuals with bowel ostomy: a systematic review - Joana Portela; Graça Melo; Tânia Mendes; Helga Rafael Henriques (Journal of Research in Nursing, 2026)
Background: Bowel ostomies pose major physical and psychosocial challenges. Self-efficacy supports ostomy self-care, and nurses play a central role through education, training and ongoing support. Aim: To synthesise evidence on nurse-led interventions that enhance self-efficacy and psychosocial adjustment in adults with bowel ostomy and to identify intervention components and delivery characteristics. Methods: A systematic review followed the Joanna Briggs Institute (JBI) methodology and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines. Searches were undertaken in five databases (CINAHL, PubMed, Scopus, Web of Science and Cochrane Library) and grey literature (December 2024). Two reviewers independently extracted and appraised data using JBI tools, with results narratively synthesised. Results: Fourteen studies were included. Nurse-led, multicomponent interventions combining education, training, follow-up and psychosocial support were most effective. Hybrid delivery and post-discharge follow-up strengthened outcomes. Most programmes were unidisciplinary, whereas multidisciplinary approaches provided broader psychosocial benefits. Heterogeneity across studies limited quantitative synthesis. Conclusion: Nurse-led, multicomponent interventions enhance self-efficacy and psychosocial adjustment, particularly when hybrid, sustained and informed by the theoretical domains framework (TDF). However, the evidence is limited by small sample sizes, heterogeneity of interventions and risk of bias in some studies. Policies should embed these interventions into standard care, emphasising continuity and digital inclusion.